2003
DOI: 10.1172/jci200316814
|View full text |Cite
|
Sign up to set email alerts
|

Application of a mathematical model to prevent in vivo amplification of antibiotic-resistant bacterial populations during therapy

Abstract: Development and owns stock and stock options. James B. Kahn is an employee of OrthoMcNeil Pharmaceutical and owns stock and stock options. Nonstandard abbreviations used: minimum inhibitory concentration (MIC); Mueller-Hinton II broth (MHB); minimum bactericidal concentration (MBC); area under the concentration time curve (AUC); nonparametric expectation maximization 2 (NPEM2); maximum a posteriori probability (MAP); quinolone resistance-determining region (QRDR).caused by antibiotic-resistant bacteria are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 224 publications
(62 citation statements)
references
References 27 publications
1
61
0
Order By: Relevance
“…A. Ferran, M. Z. Lacroix, P. L. Toutain, and A. BousquetMélou, submitted for publication). In addition, a set of published works on the influence of inoculum size on the in vivo efficacy of fluoroquinolones or beta-lactams against various Gram-positive or Gram-negative pathogens (11,15,17,19,23) supports the hypothesis that efficacious doses can be lower in early than in later interventions. In particular, Mizunaga et al (11) determined that the 50% effective doses (ED 50 s) of 3 carbapenems were 12 to 50 times lower in Pseudomonas aeruginosa-infected mice when the initial bacterial inoculum was 100-fold lower.…”
Section: Discussionmentioning
confidence: 85%
“…A. Ferran, M. Z. Lacroix, P. L. Toutain, and A. BousquetMélou, submitted for publication). In addition, a set of published works on the influence of inoculum size on the in vivo efficacy of fluoroquinolones or beta-lactams against various Gram-positive or Gram-negative pathogens (11,15,17,19,23) supports the hypothesis that efficacious doses can be lower in early than in later interventions. In particular, Mizunaga et al (11) determined that the 50% effective doses (ED 50 s) of 3 carbapenems were 12 to 50 times lower in Pseudomonas aeruginosa-infected mice when the initial bacterial inoculum was 100-fold lower.…”
Section: Discussionmentioning
confidence: 85%
“…Other factors, such as quorum sensing, decreasing expression of selected penicillin-binding proteins, and expression of autolysins, have been reported to be related to the inoculum effect (11-13); these factors were not explored in the present study. In addition, Jumbe et al (14) showed that a substantially higher drug exposure was required to suppress resistance for high-CFU inocula, as the high CFU exceeded the inverse of the mutation frequency. However, we did not evaluate the mutation frequency in time-kill studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, also in line with the previous study, the first 48 h of the experiment did not demonstrate any mutations in the target site. All organisms mediated resistance through efflux pump upregulation, as seen previously (11).…”
Section: Suppressing Resistant Mutant Amplification With Dosing (Thermentioning
confidence: 56%
“…The first demonstration of resistance suppression in vivo or in vitro was performed in a murine thigh infection model (11) and an in vitro pharmacodynamic model (8). Pseudomonas aeruginosa was the challenge strain and levofloxacin the drug employed in the animal model (11) and moxifloxacin the drug employed in the in vitro model (8).…”
Section: Suppressing Resistant Mutant Amplification With Dosing (Thermentioning
confidence: 99%
See 1 more Smart Citation